2010
DOI: 10.1016/j.quascirev.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of Southern Ocean processes in orbital and millennial CO2 variations – A synthesis

Abstract: a b s t r a c tRecent progress in the reconstruction of atmospheric CO 2 records from Antarctic ice cores has allowed for the documentation of natural CO 2 variations on orbital time scales over the last up to 800,000 years and for the resolution of millennial CO 2 variations during the last glacial cycle in unprecedented detail. This has shown that atmospheric CO 2 varied within natural bounds of approximately 170-300 ppmv but never reached recent CO 2 concentrations caused by anthropogenic CO 2 emissions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 99 publications
(154 reference statements)
7
135
0
1
Order By: Relevance
“…In addition, a rapid drop of about 10 ppmv within 350 y is found at the beginning of this transition comparable in duration and magnitude to a rapid increase found during the last deglaciation (21). Various processes are candidates to explain changes of CO 2 , such as the remarkable CO 2 decrease during the MIS 5-4 transition, or the millennial-scale variations associated with the CDM (6,22). In the following, we discuss mechanisms that could potentially explain the increase of the lag of CDM relative to the DO event from MIS 5 to 3 as identified in our CO 2 records and, hence, focus on the CO 2 increase after the DO events which explains-in case of the MIS 3 CDM-about one-third of the total CDM amplitude.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, a rapid drop of about 10 ppmv within 350 y is found at the beginning of this transition comparable in duration and magnitude to a rapid increase found during the last deglaciation (21). Various processes are candidates to explain changes of CO 2 , such as the remarkable CO 2 decrease during the MIS 5-4 transition, or the millennial-scale variations associated with the CDM (6,22). In the following, we discuss mechanisms that could potentially explain the increase of the lag of CDM relative to the DO event from MIS 5 to 3 as identified in our CO 2 records and, hence, focus on the CO 2 increase after the DO events which explains-in case of the MIS 3 CDM-about one-third of the total CDM amplitude.…”
Section: Resultsmentioning
confidence: 75%
“…Changes in ocean circulation and the distribution of major water masses can influence atmospheric CO 2 concentrations (22,26). One proxy for ocean hydrographic changes is the Nd isotope ratio in ocean sediment cores (expressed as ε Nd ), which traces deep water origin at the drill site (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that atmospheric δ 13 C provides useful constraint on the mechanisms of deglacial CO 2 rise (Schmitt et al, 2012;Joos et al, 2004;Fischer et al, 2010). Simulated atmospheric δ 13 C drops from the LGM level of about −6.4 ‰ to the minimum value of −6.7 ‰ between 16 and 14 ka (Fig.…”
Section: Simulations Of Termination Imentioning
confidence: 95%
“…Multiple processes operate simultaneously, and interact with each other non-linearly (Köhler et al, 2005;Brovkin et al, 2007;Sigman et al, 2010;Fischer et al, 2010;Tschumi et al, 2011), allowing for a wide range of possible scenarios to explain observed natural changes in atmospheric CO 2 . Furthermore, Goodwin et al (2011) point out that the way in which different climate proxies combine is crucial for accurate past carbon cycle reconstructions.…”
Section: Introductionmentioning
confidence: 99%